AJAG 2021
DOI: 10.17576/ajag-2021-15-02
|View full text |Cite
|
Sign up to set email alerts
|

Does Compliance Strategy Increase Compliance? Evidence from Malaysia

Abstract: Due to the significance of tax revenue as the primary source of a country's income, any leakage due to non-compliance behaviour may impact the country, which will eventually affect citizens. One way to reduce tax non-compliance is through compliance strategies which can be categorised into two; deterrence and accommodative approach. It is advisable that tax authority should not only focus on the deterrent approach (tax audit and penalty), mainly on tax offenders. Instead, tax authority also needs to find ways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…This explains the relationship between the research variables and the attribution theory that internal factors can influence TC in carrying out its tax obligations. These findings support the research of Hassan et al, (2021), Sari & Rejeki (2021). These findings imply that DGT must increase taxpayer understanding of tax regulations if it wants to increase TC in carrying out its tax obligations.…”
Section: The Influence Of Utr On Tcsupporting
confidence: 85%
See 1 more Smart Citation
“…This explains the relationship between the research variables and the attribution theory that internal factors can influence TC in carrying out its tax obligations. These findings support the research of Hassan et al, (2021), Sari & Rejeki (2021). These findings imply that DGT must increase taxpayer understanding of tax regulations if it wants to increase TC in carrying out its tax obligations.…”
Section: The Influence Of Utr On Tcsupporting
confidence: 85%
“…The studies show that the influence of UTR is still being debated, such as the students of Hassan et al, (2021), Sari & Rejeki (2021), stating that there is an effect of UTR on TC. On the contrary, Ghani et al, (2020), Laura & Akhdi (2021), and Ramadhan et al, (2019) mention that UTR does not contribute positively to increasing TC.…”
Section: Research Gapmentioning
confidence: 99%
“…In Malaysia, Abu Hassan et al, (2021) conducted a study to examine tax compliance strategies, including the deterrence approach involving tax audits and penalties and the accommodative approach involving tax reform to foster taxpayer compliance. The findings revealed that individual taxpayers perceive the compliance strategies provided by the Inland Revenue Board of Malaysia (IRBM), such as the Special Voluntary Disclosure Program (SVDP), positively, and that perception has a direct positive relationship with tax compliance.…”
Section: Tax System Reform and E-commerce Business Voluntary Tax Comp...mentioning
confidence: 99%
“…A country needs to secure adequate funding so that the government's development and infrastructure projects can be performed accordingly. This is essential to ensure the continuous growth of a country and the well-being of its citizens (Hassan et al, 2021;Hartner et al, 2008). Notwithstanding, that tax revenue has been declining over the past decade as depicted in Figure 1 despite of increase in gross national income.…”
Section: Introductionmentioning
confidence: 99%